Cholesterol regulatory effects and antioxidant activities of protein hydrolysates from zebra blenny (Salaria basilisca) in cholesterol-fed rats. Issue 7 (8th July 2015) - Ktari, Naourez; Belguith-Hadriche, Olfa; Ben Amara, Ibtissem; Ben Hadj, Aïda; Turki, Mouna; Makni-Ayedi, Fatma; Boudaouara, Tahia; El Feki, Abdelfattah; Boualga, Ahmed; Ben Salah, Riadh; Nasri, Moncef
<x xml:space="preserve">Abstract</x> This study aims to explore the hypocholesterolemic effects and antioxidative activities of zebra blenny protein hydrolysates (ZBPHs) in rats fed with a hypercholesterolemic diet.